The Effect of Attitude and Trust on Repurchase Intention Moderated by Flash Sale - Novita Sari; Nurhadi Nurhadi (BASKARA : Journal of Business and Entrepreneurship, 2025)
The focus of this research is on Generation Z consumers in Surabaya who utilize Shopee Food services. The study investigates several variables, which include two independent variables attitude (X1) and trust (X2) a moderating variable, namely flash sale promotion (Z), and a dependent variable, namely repurchase intention (Y). Each variable was measured using a set of indicators evaluated on a five-point Likert scale, ranging from 1 (Strongly Disagree) to 5 (Strongly Agree). The population of this research comprises Generation Z individuals living in Surabaya who have previously used Shopee Food. The study employed a non-probability sampling method with a purposive sampling technique, which was selected based on specific criteria: respondents had to have taken part in a Shopee Food flash sale program and used the service at least twice. Based on data from the Central Statistics Agency (BPS, 2023), the number of Generation Z individuals in Surabaya aged 11 to 26 years was recorded at 914,842 people. Applying the Slovin formula with a 7% margin of error, the required sample size was calculated to be 204 respondents, which was then rounded up to 205 to ensure adequate representation of the target population. The findings of this study show that consumer attitude and trust have a favorable and significant effect on repurchase intention.Trust in Shopee Food's service quality and transaction security significantly enhances repurchase intentions among customers. However, flash sale promotions can weaken these influences, leading to impulse purchases and increased customer switching to other platforms. Despite positive attitudes and trust, flash sales can hinder long-term loyalty